2006
DOI: 10.1111/j.1600-0668.2005.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of exhaled droplet nuclei in a two-bed hospital ward with three different ventilation systems

Abstract: As one of the major potential sources for infectious droplet nuclei in a hospital environment, exhalation flows of an infected patient can interact with the respiratory activities of other close individuals and with the room ventilation systems. Our latest results provide information on the penetration of exhalation jets into the ambient environment in different ventilation systems. This work is useful in identifying an appropriate and effective ventilation method for removing droplet nuclei more effectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
210
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(233 citation statements)
references
References 27 publications
9
210
0
2
Order By: Relevance
“…This finding concurs with tracer gas and simulation based studies evaluating airborne infection risk [13,26] …”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This finding concurs with tracer gas and simulation based studies evaluating airborne infection risk [13,26] …”
Section: Discussionsupporting
confidence: 72%
“…Smaller particles, while remaining airborne for longer, may still deposit out onto surfaces creating a possible contact transmission risk. While very large particles (>100µm) will clearly deposit quickly, mid-range (5-100µm) particles will be influenced by the air, initially through evaporation and then subsequently by ventilation flow patterns [12,13]. As a result, the final destination of an airborne pathogen may be many meters away from its original source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies such as Wan and Chao (2005) showed that the thermal plumes could create temperature and also density gradients in the air. They could also significantly affect the contaminant dispersions, as reported by Qian et al (2006). Qian et al (2006) also showed that contaminants injected laterally from the patient had dispersion patterns different from those injected vertically upward.…”
Section: Limitations From the "Empty Room" Simplificationmentioning
confidence: 73%
“…They could also significantly affect the contaminant dispersions, as reported by Qian et al (2006). Qian et al (2006) also showed that contaminants injected laterally from the patient had dispersion patterns different from those injected vertically upward. The injection could be affected by the heat plume generated by the real patient/thermal manikin, which implies that the effects of injection orientation should be investigated in conjunction with heat plumes.…”
Section: Limitations From the "Empty Room" Simplificationmentioning
confidence: 73%